Organic Miracle in Glasshouse - Vazirov, Polad (ADA University, 2018)
Currently, greenhouse commercial farming is rapidly growing industry in a modern globalized world. It provides great opportunity and control over the growing environment of various crops. Keeping vital factors such as temperature, levels of light and shade, irrigation, fertilizer system, humidity under the control by using technical and specification of greenhouse design it is possible to take the advantage of greenhouses. Simply, greenhouse is used to overcome deficiency in the growing qualities. Greenhouse enables certain crops to be grown all through the year regardless of the climatic conditions. There are several reasons for choosing this type of business: - First of all, over 50 % of the Azerbaijan Population depends on agriculture for their incomes and livelihoods; - The country has a very suitable environment for building such greenhouses - Russian (neighbor country with 150 million population) vegetable markets mostly depends on foreign suppliers from Turkey and Azerbaijan. - Agriculture is considered as the second leading income generating mechanism for the country. - According to the real examples, this business is profitable since people are glowingly interested in buying vegetables whole year-round. Agricultural industry including greenhouse farming is well known and is among the main leading industries in most countries of the world. Because of the significant role the agriculture sector plays, the government of most countries ensures farmers that they will be supported all the way. Mostly government support consists of giving free seedlings, fertilizers and farming instruments. Tomato growing using greenhouse technology is steadily picking up in the country and the main objective of this project is to profitably position in this industry by producing quality products and aggressively marketing it to the customers. The customers of the products will include markets, supermarkets, open air markets, groceries and independent retailers, customers buying from the farm and customers who sell our products in foreign markets. The advantages of greenhouse method of farming include: - High tomato and cucumber yield - Reduced disease attack - Costs will be low due to operating system - Stable production of the crop regardless of the prevailing season. - Uniformity of crops in terms of size and quality
Keywords: Business; Greenhouse management.; Greenhouse management -- Azerbaijan.; Floriculture -- Azerbaijan.